Analisa Perancangan Sistem Informasi Akuntansi dalam pengelolaan Laporan Keuangan pada Perusahaan - Sumaryanto Sumaryanto; Purwati Purwati; Setiyo Prihatmoko (Bridge : Jurnal Publikasi Sistem Informasi dan Telekomunikasi, 2024)
Computer-based Accounting Information Systems (AIS) have become a vital element in managing organizational finances in the digital era. To explore the role and benefits of computer-based AIS in increasing efficiency, accuracy and transparency of financial reports. By integrating information technology in the accounting process, AIS enables real-time data collection, processing and analysis, thereby supporting faster and data-based decision making, while also identifying challenges faced in implementing AIS, such as user training needs and issues. data security. That computer-based AIS not only speeds up transaction recording and information management, but also increases collaboration between departments and allows for more accurate and timely reporting. Therefore, computer-based AIS has proven to be an important strategic tool for organizations to improve financial performance and competitiveness in increasingly competitive markets.